Family and health evolving needs, responsibilities, and experiences - McCormick, Jennifer Higgins; Blair, Sampson Lee. (Bingley, U.K. : Emerald, 2014)
Around the globe, families are often faced with a variety of health issues, often as a result of social, political, religious, and economic forces. Health issues affect both individual family members and the family unit as a whole, as well as impacting family relationships and structures. Illnesses, injuries, and health problems can strike at any time, and can have long-lasting consequences for individuals and their families. This multidisciplinary volume addresses the impact health issues have on individual family members and how this affects their family relationships. The chapters cover a wide range of health related topics including illness in adults and children, long term illness, mental health, and international perspectives. Through the use of a wide variety of methodological and theoretical perspectives, the family scholars in this volume provide considerable insight into the ways in which families and their members are affected by health, as well as how they adapt to and cope with health-related dilemmas.
A multi-level analysis of psychological well-being related to work and family in 33 countries / Makiko Hori, Yoshinori Kamo -- The influence of family socioeconomic status on health care professional recommendations of the HPV vaccine / Hanna Jokinen-Gordon -- Multiple motherhoods : the effect of the internalization of motherhood ideals on life satisfaction / Kayla M. Pritchard, Lisa A. Kort-Butler -- The lived experiences of daughters of women with breast cancer / Amanda C. Ginter, M. Elise Radina -- Demographic trends and the healthcare system in Moldova : reforms and challenges / Valentina Bodrug-Lungu, Erin Kostina-Ritchey -- Long-term care needs and long-term care policy : comparing Germany and Israel / Monika Reichert ... [et al.] -- An examination of the effects of current obstetrical opinions, diagnostic and practice trends in the management of twin to twin transfusion syndrome patients / Lauren Nicholas -- Stress and support among people caring for homeless adult relatives / Michael F. Polgar, Carol S. North, David E. Pollio -- Depressive symptomology among rural low-income Latina and non-Latina white mothers / Jacy Downey, Kimberly Greder -- From boys to men : shifting family gender ideologies among black and white adult men / Myron T. Strong, Erma Lawson.
Print version record
Keywords: Social Science -- Sociology / Marriage & Family; Family & Relationships -- General; Sociology: family & relationships; Family & health; Families -- Health and hygiene